BIOMARKER SIGNIFICANCE OF CIRCULATING DNA ACCORDING TO LIQUID BIOPSY IN PATIENTS WITH PREGNANCY-ASSOCIATED CANCER AND UROGENICOLOGICAL CANCER - Komarevtsev, V.M.; Balabanova, K.V.; Chernykh, Yu.A.; Kalinin, I.V.; Komarevtseva, I.O.; Cherednichenko, R.V.; Seryogina, N.M. (World of Medicine and Biology, 2025)
The purpose of the study was to investigate the role of the biomarker of circulating cell-free DNA in the the development of pregnancy-associated renal cell carcinoma and pregnancy-associated uterine sarcoma within 1 years (56 weeks) after childbirth. To test our hypothesis, this case-control study consisted of the indicators of cfDNA in the blood serum of 16 patients with pregnancy-associated renal cell carcinoma; 38 patients with renal cell carcinoma; 8 patients with pregnancy-associated uterine sarcoma and 11 patients with uterine sarcoma. We have established a high level of circulating cell-free DNA in sick women, both renal cell carcinoma and uterine sarcoma, as well as the pregnancy-associated renal cell carcinoma and pregnancy-associated uterine sarcoma, at all stages of the tumor process. in our study, The mathematical prognostic model of changing circulating cell-free DNA levels in women during the year after childbirth within 26–36 weeks and 40–41 weeks, confirmed a high and moderate risk of developing pregnancy-associated cancer in the first 12–24 weeks after childbirth, which corresponds to the time diagnostics of the pregnancy-associated cancer in our study. The pathogenetic platform of the development of pregnancy-associated cancer is a high level of circulating cell-free DNA in women during pregnancy and the first 12–24 weeks after birth in a period of 40–41 weeks and especially with premature birth in 26–36 weeks
Keywords: circulating cell-free DNA; pregnancy-associated renal cell carcinoma; pregnancy-associated uterine sarcoma